Impacto de las remesas de los peruanos residentes en Japón - Vela Borda, Joel (2006)
This study analyzes the significance of remittances from Peruvian residents in Japan to Peru to their families and the Peruvian economy at large, as well as the extent to which such financial assistance is contributing to the livelihood of numerous individuals and to improving their qualityof living. More generally, it addresses the financial impacts of these remittances, the costs involvedand how they have evolved over time. The study starts by briefly presenting present Japanese economy because although Japan has not experienced noteworthy economic growth in recentyears, it is still a world economic powerhouse. It then explains how after more than a century of Japanese migration to Peru, Peruvians of Japanese descent have started to return to the Land of the Rising Sun in search of better fortune.